A Time-Varying Radiometric Bias Correction for the TRMM Microwave Imager - Gopalan, Kaushik; Jones, W. Linwood; Biswas, Sayak K.; Bilanow, Stephen; Wilheit, Thomas T.; Kasparis, Takis (My University, 2009)
Recent intersatellite radiometric comparisons of the Tropical Rainfall Measurement Mission Microwave Imager (TMI) with polar orbiting satellite radiometer data and modeled clear-sky radiances have uncovered a time-variable radiometric bias in the TMI brightness temperatures. The bias is consistent with a source that generally cools during orbit night and warms during sunlight exposure. The likely primary source has been identified as a slightly emissive parabolic antenna reflector. This paper presents an empirical brightness temperature correction to TMI based on the position around each orbit and the Sun elevation above the orbit plane. The results of radiometric intercomparisons with WindSat and special sensor microwave imager are presented, which demonstrate the effectiveness of the recommended correction approach based on four years of data.
Keywords: Intersatellite radiometric calibration; Microwave radiometer; Special sensor microwave imager (SSMI); Tropical Rainfall Measurement Mission Microwave Imager (TMI); WindSat